PENGARUH KUALITAS LAYANAN TERHADAP E-LOYALTY PENGGUNA LAYANAN APLIKASI FINTECH MELALUI KEPUASAN PENGGUNA SEBAGAI VARIABEL INTERVENING (STUDI PADA GENERASI Z PENGGUNA APLIKASI FINTECH FLIP DI JAKARTA). - Najla Indira Hajida; Bulan Prabawani (Jurnal Ilmu Administrasi Bisnis, 2025)
Flip application is a digital financial service in Indonesia which is a pioneer provider of free interbank transfer services and has more than 13 million users. Consumer loyalty usually arises marked by the satisfaction of users with existing services. That means, if the user is satisfied with the services and services provided, it will provide additional value to the service provider.  However, the Flip app cannot maintain loyalty. This is indicated by the decline in quality and customer satisfaction which causes loyalty to decline. This research type is explanatory research. Meanwhile, the respondents in this study were 97 respondents with nonprobability sampling technique purposive sampling method. The data that has been collected is then processed using data analysis techniques including validity test, reliability test, fit model, r-squared, f-squared, path coefficient, and VAF mediation test. The conclusion of this study shows that service quality has a positive and significant effect on e-loyalty through user satisfaction as an intervening variable. This study suggests that the Flip application make improvements to service performance performance, be responsive in responding to user complaints, evaluate service performance and quality of applications, supervise services, and evaluate the performance of the customer service team.